Building upon the foundational science curriculum with physiology-based grand rounds: a multi-institutional program evaluation. Issue 1 (1st January 2021) - Langer, Arielle L.; Block, Brian L.; Schwartzstein, Richard M.; Richards, Jeremy B.
ABSTRACT: Introduction : Vertically integrating physiology into patient care has the potential to improve clinical reasoning. Clinical Physiology Grand Rounds (CPGR) is a case-based teaching method that brings together students from all years of medical school to focus on linking clinical presentations to core basic science concepts including anatomy, physiology, and pathophysiology. In this study, we describe the implementation of CPGR at two different institutions in the United States and assess student-reported outcomes. Methods : We survey students who participated in CPGR at Columbia University College of Physicians & Surgeons (P&S) and Medical University of South Carolina (MUSC). Subjects were queried across three domains: the benefits of attending, the impact of concept maps, and the impact of the mixed-learner environment. Results : Despite differences in session leadership and the underlying medical school curricula, conference attendees reported similar benefits at the two schools included in this study. Students overwhelmingly (92.9%) reported that remembering clinical presentations was easier when they understood the underlying physiology. They also reported gaining a true understanding of concepts that were previously memorized (87.5%). Both clinical (92.5%) and preclinical students (93.1%) valued the mixed-learner environment as a component of the conference. Discussion : By assuring a mixed-learner environment with near-peer interactions, using concept maps as a teaching tool, and rigorously linking clinical presentation and management to physiological concepts, we found that the key benefits of CPGR were replicable across different institutions, despite several local differences in how CPGR was implemented, led, and conducted.